POSITIONING UMMAH IN INTERNATIONAL POLITICS: A SOUTH-SOUTH PERSPECTIVE - Hadza Min Fadhli Robby (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2020)
This research would like to discuss the reconceptualization of Ummah in the context of contemporary international politics. Ummah, as a concept, has been implemented since the era of Prophet Muhammad. Since the advent of the modern era, the concept of Ummah has been deemed as irrelevant due to the existence of modern nation-state. However, newly independent countries that are having a majority of Muslim populations tried to rebuild the new consciousness among Muslim communities by establishing organizations that resemble Ummah. There are at least three endeavors noted throughout history: Asian-African Islamic Conference, Organization of Islamic Cooperation, and Developing-8 (D-8). Only two endeavors successfully emerged as an active international organization representing the Muslim community's interest in world politics. Using the English School and South-South perspective, this research tried to decipher the reason behind the creation of those organizations.